Drivers and barriers to sustainable risk management (SRM) practices in Malaysian environment sensitive listed companies / Nazliatul Aniza Abdul Aziz and Norlida Abdul Manab - Abdul Aziz, Nazliatul Aniza; Abdul Manab, Norlida (Accounting Research Institute (ARI), 2020)
Sustainable risk management (SRM) has become the most important managerial trend for business sustainability. Companies have started paying greater attention to adopt SRM towards achieving responsible patterns of consumption and production. Yet little is known about the drivers and barriers to SRM practices. This study aimed to fill this gap by identifying the drivers and barriers to SRM practices among environment sensitive listed companies in Malaysia. Data was collected through a questionnaire survey with 53 respondents and interviews with 3 persons-in-charge of the risk management department from the environment sensitive listed companies in Malaysia. The study revealed that internal factors such as stakeholder pressure and long-term shareholder value motivated the companies to adopt SRM practices. Also, the study found external factors such as corporate governance compliance and regulatory compliance as among the drivers that encourage companies to implement SRM. Nevertheless, the factors which were not perceived as a priority by the board of directors include organisational culture and lack of tools and data that constitute internal barriers to effective implementation of the SRM. The results of this study offer valuable insights to environment-sensitive companies to further understand the drivers and barriers of SRM practices which are essential to becoming sustainable companies.